The Phytochemical Constituents, Antioxidant and Antidiabetic Efficacies of the Crude Extract and Fractions of Ethulia conyzoides Leaves: Crude Extract and Fractions of Ethulia conyzoides Leaves - Helen Omasan Okotie; Tayo Micheal Anjuwon; Oluwafemi Abiodun Adepoju; Ijeoma Okolo; Gilead E. Forcardos; Dorcas Bolanle James (Journal of Tropical Life Science, 2022)
Ethulia conyzoides is a plant traditionally used in managing diabetes in Nigeria. Unfortunately, its antidiabetic potential has not been scientifically examined. The research investigated the phytochemical constituents, in vitro antioxidant and antidiabetic efficacies of Ethulia conyzoides leaves extract. Seventy percent (70%) methanol extraction of E. conyzoides leaves was done to obtain its crude extract and then was partitioned with n-hexane and ethyl acetate to obtain three fractions (n-hexane, ethylacetate and residual aqueous). Then, they were subjected to various phytochemistry investigations: 1,1-diphenyl 2-picryl hydrazyl (DPPH) radical scavenging activity assay and in vivo antidiabetic effects in mice. The fasting blood glucose (FBG) levels, weight change, feed and fluid intakes were determined using standard procedures. Phyto-profiles tests for the extract and its fractions revealed the presence of phenolics, tannins, cardiac glycosides, saponins and alkaloids. The result showed that residual aqueous fraction had the nearest inhibitory concentration (IC50) of 0.011Âµg/ml to the standard ascorbic acid with 0.010Âµg/ml when compared with other extract and fractions. There were substantial (p<0.05) rise in fluid and feed intakes and serum level of FBG in the type 2 diabetic mice. Treatment of the mice using 100 mg/kg b.w. residual aqueous fraction for 21 days significantly (p<0.05) reduced the fluid intake, feed intake and FBG and statistically (p<0.05) improved the body weight. This study revealed that the residual aqueous fraction of Ethulia conyzoides have antioxidant and antidiabetic activities against induced type 2 diabetic mice.